Dual Target Anticancer Potential of Exiguobacterium-derived Metabolites from the Maros-Pangkep Karst: An In Silico Study Targeting EGFR and Caspase-3 - Taswin Wijaya; Nur Haedar; Helmy Widyastuti; Riuh Wardhani; Fuad Gani (Molecular and Cellular Biomedical Sciences, 2026)
Background: Cancer is the second leading cause of death worldwide, and its multifactorial nature limits the effectiveness of single-target therapies. Combination treatments may improve efficacy but are often associated with toxicity and drug interactions. Extremophilic bacteria from karst environments remain underexplored as sources of multitarget anticancer compounds. This study aimed to evaluate the dual-target anticancer potential of bioactive metabolites produced by bacteria isolated from the Maros–Pangkep karst region using molecular docking and ADME analysis.Materials and Methods: A bacterial isolate obtained from soil samples from the Maros–Pangkep karst region, Indonesia, was selected based on colony morphology and identified as Exiguobacterium using 16S rRNA gene analysis. Bioactive compounds were characterized by GC-MS, and three major metabolites were docked against EGFR (PDB ID: 1M17) and caspase-3 (PDB ID: 1PAU). ADME analysis was performed to evaluate drug-likeness and toxicity.Results: Docking analysis showed that compound (1) Pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) exhibited the strongest binding affinity toward EGFR (−7.2 kcal/mol), exceeding the native ligand erlotinib (−6.1 kcal/mol). Compound (2) Cyclo(L-prolyl-L-valine) and compound (3) 2,5-piperazinedione,3-methyl-6-(1-methylethyl) derivatives showed binding affinities of −6.4 and −5.9 kcal/mol, respectively. For caspase-3, the compounds displayed binding affinities ranging from −4.5 to −6.0 kcal/mol , exceeding the native ligand Ac-DEVD-CHO (−3.6 kcal/mol) and interacted outside the active site, indicating potential allosteric activation. All compounds complied with Lipinski’s rule of five and showed low toxicity (LD50>800 mg/kg).Conclusion: This study shows that metabolites from Exiguobacterium possess dual-target anticancer potential via EGFR inhibition and caspase-3 modulation, suggesting their use as multitarget drug candidates. Keywords: 16S rRNA, bacteria, biological products, caspase-3, epidermal growth factor receptor, Kart Maros-Pangkep, molecular docking